Addressing hospitalisations with non-error-free data by generalised SEIR modelling of COVID-19 pandemic - Mendes, Jorge M. (2021)
Mendes, J. M., & Coelho, P. S. (2021). Addressing hospitalisations with non-error-free data by generalised SEIR modelling of COVID-19 pandemic. Scientific Reports, 11(1), 1-20. [19617]. https://doi.org/10.1038/s41598-021-98975-w